Rural youth sustainable livelihood: some preliminary results - Md. Yassin, Sulaiman; Hamzah, Azimi; Abu Samah, Bahaman; Abu Samah, Asnarulkhadi; Idris, Khairuddin; Kamaruddin, Nurani; Mohamed Shaffril, Hayrol Azril (Medwell Journals, 2014)
This study attempts to examine the rural youth sustainable livelihood phenomena in Malaysia. The results presented in the present study were the preliminary data which gained through the pre-test process. The pre-test was conducted among 30 rural youths in Kuala Besut, Terengganu. Out of 6 capitals studied, 3 of them recorded high levels of mean scores while the other 3 capitals recorded a moderate level of mean scores. The human capital recorded the highest mean score, however yet the strength possessed in human capital cannot assist them to strengthen their financial capital as this capital recorded the lowest mean score. Though results discussed only demonstrate the preliminary findings, however yet the results are expected to portray a possible prediction of what actual data would be.